The early days of public relations in British Malaya: winning the hearts and minds of the Empire - Souket, Rizwanah; Syed Abdullah Idid, Syed Arabi (Elsevier Ltd, 2020)
This article traces the early form of public information services during the colonial period to provide new insights into the historical development of Malaysia’s public relations. The first formal information agency created in 1910 was based in London to promote the early practices of public relations for British Malaya and its interests in Britain. British consolidation during the years of economic boom and depression, until the achievement of Malaysian Independence, was aided by the early information services. The article makes an alternative argument about the beginnings of Malaysian public relations based on colonial economic and political interest as against other previously held views